The first observations of the cold intermediate layer on shelf Antarctic peninsula - Neverovsky, I.P.; Popov, Y. I.; Sytov, V.N.; Matygin, A. S. (Ukrainian Antarctic Journal, 2015)
The structure of the water masses in the region Argentine Islands archipelago was first investigated according to the data detailed oceanographic survey, which was conducted during the period of the 17th Ukrainian Antarctic Expedition (2012-2013). Formation of а three-layer structure of water masses in summer were observed in the Penola Strait, the cold intermediate layer of negative temperature was found for the first time . This layer separates relatively warm and significantly more salty deep-waters from the warmed up in summer conditions and freshened surface waters. Higher salinity of deep waters does not allow to go down of the cold waters of the intermediate layer оn the greater depths, so they are spread in the subsurface horizons. Summer the Antarctic cold intermediate layer (ACIL) is defined as а layer of negative temperatures, the temperature in the core is lower than -0.35 °С. ACIL located in the Strait of Penola in а layer of seasonal jump in density at а depth of 25-80 meters. Outlet glaciers are the source of generation ACIL оn western shelf of the areas Antarctic Peninsula. The volume-statistical analysis the Т, S-diagrams showed the existence of transfer to the water area of Argentine Islands of the intermediate-deep waters of the Вау Margaret, which is located to the south of the archipelago.